On impact of channel estimation error in cognitive radio network with wireless energy harvesting - Nguyen , Tan Loi; Nguyen , Thi Khanh Tuyen; Do , Dinh Thuan (Journal of Technical Education Science, 2016)
In this paper, impact of channel estimation error in wireless energy harvesting network is evaluated through spectrum sharing model for cognitive radio networks. In the model system, the secondary user acting as relay nodes can scavenges energy from the received primary signal, then use the energy obtained to transfer the remaining primary signal to destination and secondary information to other secondary users. Relay node uses decode and forward (DF) to transmit information. In relay node exist interference due to channel state information (CSI) error. Performance of the model was evaluated through outage probability. Through analysis, the paper offers the exact expression of the outage probability for both the primary and secondary network. Besides that, this investigation also shows the influence of the energy distribution to signal transfer capacity. The result of the outage probability, the energy distribution is suitable for the proposed protocol enables achieve better performance compared with direct transmission without spectrum sharing, and do not consume more energy supplied to the relay node.